Rates of hospitalization associated with the use of aldosterone receptor antagonists in patients with pulmonary arterial hypertension - Morgan E. Corkish; Lauren T. Devine; Megan M. Clarke; Brian P. Murray; Lisa J. Rose-Jones (Pulmonary Circulation, 2019)
We show that spironolactone use was associated with an increased rate of all-cause hospitalizations, but no difference in hospitalizations for heart failure or pulmonary arterial hypertension, in patients with World Health Organization Group 1 pulmonary arterial hypertension. A possible reason for this finding is confounding from retrospective study design.